2018
DOI: 10.5206/cie-eci.v47i1.9322
|View full text |Cite
|
Sign up to set email alerts
|

From Class Assignment to Friendship: Enhancing the Intercultural Competence of Domestic and International Students through Experiential Learning

Abstract: This study explored growth in the intercultural competence of domestic and international students who participated in an intercultural experiential learning initiative for academic credit. The initiative paired Canadian students in a second-year multiculturalism class at Wilfrid Laurier University with international students enrolled in the Laurier English and Academic Foundation (LEAF) program. Qualitative data derived from the oral and written reflections of three cohorts of students inform the study. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Similarly, research on interactions of international and domestic students has found that experiential learning courses, collaborative group projects, and the formation of friendships can lead to intercultural knowledge and skills as well as increased outgroup understanding for both domestic and international students (Parsons, 2010;Wilson-Forsberg et al, 2018). Similar to research on intergroup contact, research on internationalization highlights the potential for negative outcomes from contact across cultures (e.g., Nyunt et al, 2022).…”
Section: Intergroup Contact Theory and Virtual Exchangesmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, research on interactions of international and domestic students has found that experiential learning courses, collaborative group projects, and the formation of friendships can lead to intercultural knowledge and skills as well as increased outgroup understanding for both domestic and international students (Parsons, 2010;Wilson-Forsberg et al, 2018). Similar to research on intergroup contact, research on internationalization highlights the potential for negative outcomes from contact across cultures (e.g., Nyunt et al, 2022).…”
Section: Intergroup Contact Theory and Virtual Exchangesmentioning
confidence: 93%
“…Intergroup contact undergirds many of the internationalization efforts on college campuses, including study abroad (Brajkovic & Matross Helms, 2018;Hudzik, 2015;Knight & de Wit, 2018) and interactions of domestic and international students (Parson, 2011;Wilson-Forsberg et al, 2018). Research on study abroad participation generally finds links between studying abroad -in particular interactions with host nationals -and the development of intercultural competence, global awareness, and interest in further intercultural engagement (Haupt & Ogden, 2019;Nyunt, 2021;Nyunt et al, 2022).…”
Section: Intergroup Contact Theory and Virtual Exchangesmentioning
confidence: 99%
“…A growing body of research on university study abroad programs demonstrates that optimal learning takes place beyond the student’s comfort zone (Benham Rennick and Desjardins, 2013; Curran et al, 2019; Dorsett et al, 2019; Trilokekar and Kukar, 2011; Wilson-Forsberg et al, 2018). It further demonstrates how some students use varied psychological strategies to navigate cultural differences and disorientation to advance along the intercultural learning continuum, while others remain at the same level of intercultural learning or regress (Mitchell and Paras, 2018).…”
Section: An Ethic Of Discomfortmentioning
confidence: 99%
“…Finally, Piaf (pseudonym) summarized the impact of global exposure by proclaiming "with a renewed sense of humility, students will posses a boldness to know how to be a Chris2an in the realworld environment." Through inten2onal design based on exis2ng programs and research studies, study abroad experiences have the poten2al to create global ci2zens who exhibit characteris2cs of intercultural competence -"the ability to develop targeted knowledge, skills, and aktudes that lead to visible behavior and communica2on that are both effec2ve and appropriate in intercultural interac2ons" (Wilson-Forsberg et al, 2018, p. 2) -while also developing a deeper, personal understanding of their faith. Venus (pseudonym), an external stakeholder, shared that during her study abroad experience "everything is so different that you are grasping daily for anything that is familiar and comfort, which for me ended up being God and His word, which are never-changing no ma7er where you are.…”
Section: Cycle 1 Results/findingsmentioning
confidence: 99%
“…The research has shown that interna2onal learning experiences can alter the manner in which one sees and interacts with the world around them (Hill et al 2020;Jackson 2015;Wilson-Forsberg et al, 2018). Nevertheless, it was equally conclusive in Reyns-Chikuma's (2013) and Horn & Fry's (2013) studies that simply traveling to a different culture will not magically transform one's worldview.…”
Section: Skillsmentioning
confidence: 99%